Effects of a health literacy program on self-management behaviors of patients with uncontrolled type 2 diabetes in Thailand: A quasi-experimental study - Sriklo, Mathaka; Sermsinsiri, Kanchita (Belitung Raya Publisher - Belitung Raya Foundation, 2026)
Background: Uncontrolled type 2 diabetes results in major complications that threaten patients’ life. Patients with uncontrolled type 2 diabetes often have inadequate health literacy, making them less motivated to perform self-management behaviors for glycemic control. Earlier health literacy interventions were effective in promoting self-management behaviors and reducing blood glucose, but evidence is lacking for those with uncontrolled type 2 diabetes. Objective: This study aimed to investigate the effect of a health literacy program on self-management behaviors of patients with uncontrolled type 2 diabetes. Methods: This two-group quasi-experimental study with pre-posttest design was done between September 2024 and June 2025. The participants were 64 patients with uncontrolled type 2 diabetes who lived in a community in a province in central Thailand selected using simple random sampling. The experimental group (n= 32) underwent the health literacy program with eight weekly sessions along with usual care while the control group (n = 32) was given usual care only. Data were collected using a Demographic Data Questionnaire, the Functional, Communicative and Critical Health Literacy Scale, the Self-Management Behavior Scale, and hemoglobin A1C (HbA1C) testing. Data analysis was performed with descriptive statistics, paired t-test and independent t-test. Results: No significant between-group differences were noted in baseline data. At post-test, the experimental group had a significantly higher mean score of overall health literacy (t = 3.720, Cohen’s d = 2.67), functional health literacy (t = 0.399, Cohen’s d = 2.43), communicative health literacy (t = 7.90, Cohen’s d = 1.76), and critical health literacy (t = 12.972, Cohen’s d = 3.14), and self-management behavior (t = 21.862, Cohen’s d = 2.84), and a significantly lower level of HbA1C (t = 3.436, Cohen’s d = -0.82) than before receiving the program and than the control group (all p <0.01). Conclusion: This study offers evidence for the program's efficacy in raising health literacy, which in turn improves self-management behavior and decreases HbA1C in patients with uncontrolled type 2 diabetes. Nurses can incorporate program activities in empowering patients for diabetes control by promoting their ability to seek and comprehend health information, communicate effectively during medical visits, and develop critical thinking abilities on diverse health determinants. Trial Registry Number: Thai Clinical Trials Registry (TCTR20250624001)